The Role of Atomic-Scale Disorder in Tailoring the Functional Properties of Crystalline Materials: A Comprehensive Review - Rahman, Md Sultanur; Uddin, Md Jasim; Hasan, Rakib; Mia, Md Mehedi Hasan (Scientific Journal of Engineering Research, 2025)
It has long been believed that crystalline solids will always have atomic-scale disorder, which includes vacancies, interstitials, andesite defects, local strain fields, short-range compositional changes, and amorphous pockets. The functional qualities of materials can be controlled by redefining disorder as a flexible and adjustable design parameter. Across classes of crystalline materials (oxides, chalcogenides, perovskites, semiconductors, and two-dimensional crystals), we synthesize experimental and theoretical advances demonstrate how particular types and distributions of atomic-scale disorder alter charge-carrier dynamics, optical absorption and emission, magnetic ordering, ionic conductivity, thermal transport, and mechanical response. Mechanistic relationships are highlighted, including how correlated defect complexes and local strain mediate polaron generation and carrier mobility, how interface disorder and grain-boundary structure control ion transport and catalytic activity, and how point defects alter electronic band edges and trap states. From total-scattering PDF analysis and advanced spectroscopies to aberration-corrected TEM, atom probe tomography, and scanning probe microscopies, we go over characterization tools and how data-driven models, large-scale molecular dynamics, and first-principles calculations are coming together to predict and direct disorder engineering. Successful methods for improving device performance such as defect-enabled light emission, dopant-activated ionic conductors, and disorder-stabilized phases are highlighted in case studies. We conclude with useful recommendations for intentional disorder design and point out unresolved issues, such as in-operando characterization, multiscale modelling, and controlled defect synthesis, providing a roadmap for utilizing atomic-scale disorder to develop next-generation functional materials.